Impact Of Primary Care Physicians' And Health Assistants Practices In Managing Overweight And Obesity In Saudi Arabia 2024 (The Review of Diabetic Studies, 2024)
BackgroundObesity is an emerging public health problem in the world, and health professionals are most likely to be exposed to several occupational, also Obesity is a global world-wide health problem in both developing and developed countries. In Saudi Arabia, this problem becomes an alarming disease both during childhood and adulthood among males and females. Primary Care Physicians’ and Health assistants managing Overweight and Obesity are identified as the first line of defense and contributor to cost-effective for the management and prevention of the disease; they are expected to normalize the weights in the community. These include long working hours, shift work, high job stress, irregular food intake, poor opportunities for healthy eating, and physical inactivity at work. Healthcare workers’ stressful jobs typically lead to poor eating habits and less opportunity for physical exercise, contributing to obesity risk, and Health assistants  are the first point of contact and one of the most important starting points for the successful treatment of being overweight or obese. The study aimed: To assess the Primary Care Physicians’ and Health assistants Practices in Managing Overweight and Obesity in Saudi Arabia 2024 Method: Cross-sectional survey was utilized   in Saudi Arabia 2024 during the November to December, 2024, a total of 300 participant aged 25– ≥ 50 years, available. A structured self-reported questionnaire sheet was used to assess in Managing Overweight and Obesity in Saudi Arabia 2024. Using a stratified random sampling techniqueResult: show regarding the primary Care Physicians’ and Health assistants Practices in Overweight and Obesity habitual factors regarding the you have any complications from obesity most of participants answer Yes (40.8%), follow by No were(59.2%) , regarding Smoking cigarette most of participant Non-smoker  were(41.2%) follow by quit smoking were (21.2%) while smoker were (38.0%), regarding the BMI status most of participant normal weight were (68,0%) followed by overweight were (11.2%) but the obese were (20.8%).Conclusion: These findings highlight Primary Care Physicians’ and Health assistants Practices in managing Overweight and Obesity. The strategy to address managing Overweight and obesity among this highly vulnerable population should be directed toward enhancing physical activities, improving eating habits, and managing occupational stress, particularly for Primary Care Physicians’ and Health assistants.